A study on the perceived organizational readiness for change of the librarians and library staff of the University of the Philippines Diliman library system - Palaya, Aiza May V. (School of Library and Information Studies, University of the Philippines Diliman, 2015)
Change is pervasive and any institution which aims to carry on with the times is left with no choice but to keep up with it. Change in the workplace may be one of the most challenging subjects to discuss as well as incorporate in previously established routines. Much like any other institution, the library goes through changes.